Front Cover: Scale‐up and Sustainability Evaluation of Biopolymer Production from Citrus Waste Offering Carbon Capture and Utilisation Pathway (ChemistryOpen 6/2019) - Durkin, Alex (ChemistryOpen, 2019)
The Front Cover shows modelling research on the co‐polymerisation of waste‐sourced limonene oxide with CO(2) to produce poly(limonene carbonate), which offers a sustainable pathway to achieve carbon capture and utilisation. A computational approach to process design was integrated with sustainability evaluation to model this synthetic pathway and identify the environmental‐damaging and performance‐limiting steps for further improvement. Our research highlights the potential of closed‐loop manufacturing systems with waste recovery, which is instrumental in building a sustainable circular economy. More information can be found in the Full Paper by A. Durkin et al. on page 668 in Issue 6, 2019 (DOI: 10.1002/open.201900015).[Image: see text]